AKAR MODERASI BERAGAMA DI PESANTREN (Studi Kasus di Ma’had Aly Sukorejo Situbondo dalam Terbentuknya Nilai-Nilai Moderasi Beragama) - Aziz, Abdul (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
Religious moderation is increasingly intensified to compensate some groups who continue to make the religious issues as object of conflict. The issue of religion is made as a commodity for political interests, even though Islam has been moderate since its inception. There is a lot of concrete evidence to show that Islam is a moderate religion. Become the mediator of religions that have been held before. Actually, when examined the moderation of Islam it has been built for a long time in Indonesia, especially in the world of islamic boarding school (pesantren). Including in Ma'had Aly (MA) Situbondo, as the institution that takes the Fiqh and Ushul Fiqh for its focus of learning studies, which is under the authority of the Salafiyah Syafi'iyah Islamic Boarding School Sukorejo Situbondo. Seeing the results of their discussion, which stated in Tanwirul Afkar Magazine, it can be seen that they are very moderate. The Fiqh that they convey is not only seen as a product, but also as a process, and that become the reason for their reasoning power of ushuly is always appears. The proposition is not only textual, but it is also contextual. Therefore from this good struggle with various kinds of fiqh madzhab and strengthened by the concept of ushul fiqh they had mastered make the moderate character formed by well.